2006
DOI: 10.1111/j.1525-1594.2006.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐engineered Approach for the Treatment of Steroid‐induced Osteonecrosis of the Femoral Head: Transplantation of Autologous Mesenchymal Stem Cells Cultured With Beta‐Tricalcium Phosphate Ceramics and Free Vascularized Fibula

Abstract: Autologous mesenchymal stem cells (MSCs) cultured with beta-tricalcium phosphate (beta-TCP) ceramics and with a free vascularized fibula were transplanted into three patients with steroid-induced osteonecrosis of the femoral head. The average follow-up period was 34 months and the average patient age at the time of surgery was 28 years old. Fifteen milliliters of bone marrow was obtained from the patients 4 weeks before surgery, and was used for in vitro proliferation of MSCs. beta-TCP granules were immersed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 9 publications
2
94
0
3
Order By: Relevance
“…Tissue-engineering approaches, including stem cells and growth factors [18,24] or externally applied signals such as stimulation with electric currents [7,11], ultrasound [10,43], or laser [28], are promising in overcoming these problems, but they also have several shortcomings. Current cell culture-based techniques require considerable resources to reach the number of required cells, bear risks for transfer of infectious diseases, and involve invasive surgery [40].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue-engineering approaches, including stem cells and growth factors [18,24] or externally applied signals such as stimulation with electric currents [7,11], ultrasound [10,43], or laser [28], are promising in overcoming these problems, but they also have several shortcomings. Current cell culture-based techniques require considerable resources to reach the number of required cells, bear risks for transfer of infectious diseases, and involve invasive surgery [40].…”
Section: Introductionmentioning
confidence: 99%
“…Cell-based treatments have advanced and have been applied for some diseases involving osteonecrosis and cartilage defects of joints (10,21,22). Recently, Kawate et al (10) applied constructs of MSCs and β-TCP ceramics to a clinical case of femoral head osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kawate et al (10) applied constructs of MSCs and β-TCP ceramics to a clinical case of femoral head osteonecrosis. They reported that the osteonecrosis did not progress any further, and early bone regeneration was observed, indicating that such a cell-based tissue engineering strategy has potential for clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical applications of tissue engineered BMSCs have been attempted in a number of therapies, including the treatment of osteonecrosis [19][20][21]. In these appro-aches, BMSCs are obtained from the patients, following which they generally need to be expanded by serial passaging in vitro as the number of cells generated in primary culture is limited.…”
Section: Introductionmentioning
confidence: 99%